A kind of sulfurized polyacrylonitrile positive electrode and its preparation method and application

Through the new preparation method of vulcanized polyacrylonitrile positive electrode, the fractured long-chain sulfur treatment is solved through secondary sintering, and the performance attenuation problem of solid sulfur positive electrode caused by the shuttle effect is achieved, achieving higher discharge specific capacity and cycle stability.

CN115799504BActive Publication Date: 2025-03-07BEIJING UNIV OF CHEM TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211639494.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-20
Publication Date
2025-03-07
Estimated Expiration
2042-12-20

AI Technical Summary

Technical Problem

During the discharge process, the solid-liquid-solid positive electrode leads to a shuttle effect, resulting in continuous consumption of active substances and rapid attenuation of performance. At the same time, the insulation of sulfur leads to a low utilization rate of active substances.

Method used

A new method for preparing a positive electrode of vulcanized polyacrylonitrile is adopted. By dissolving polyacrylonitrile in an organic solvent and mixing with vulcanized polyacrylonitrile and acetylene black, uniformly coating it on aluminum foil, and undergoing a secondary sintering process to break the long-chain sulfur to form short-chain sulfur, improving the utilization rate of active substances.

Benefits of technology

With the unchanged sulfur content, the discharge specific capacity and cycle stability of the vulcanized polyacrylonitrile positive electrode are improved, the cycle life of the battery is extended, and the preparation cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004008156740000011
    Figure HDA0004008156740000011
  • Figure HDA0004008156740000012
    Figure HDA0004008156740000012
Patent Text Reader

Abstract

The present invention provides a method for preparing a sulfurized polyacrylonitrile positive electrode, which is carried out according to the following steps: (1) dissolving polyacrylonitrile in an organic solvent, stirring until the polyacrylonitrile is completely dissolved, and obtaining a polyacrylonitrile solution; (2) mixing and stirring the sulfurized polyacrylonitrile, acetylene black and the polyacrylonitrile solution obtained in step (1) to obtain a mixture of sulfurized polyacrylonitrile / acetylene black / polyacrylonitrile; (3) coating the mixture obtained in step (2) evenly on an aluminum foil, drying and cutting it into a positive electrode sheet; (4) placing the positive electrode sheet obtained in step (3) in a sealed glass tube, heating and reacting at 200-350°C in an air environment, and after the reaction is completed, taking it out and cooling it naturally. The present invention also provides a sulfurized polyacrylonitrile positive electrode prepared by the above method and its application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of secondary batteries, and in particular to a sulfurized polyacrylonitrile positive electrode and a preparation method and application thereof. Background Art

[0002] New secondary batteries with high energy density, high safety, long cycle life and low cost have always been an urgent need for electrochemical storage devices such as portable electronic products and electric vehicles. Lithium-sulfur batteries (Li-S) have attracted much attention due to their great advantages such as high specific energy density, low cost and environmental protection, and are considered to be one of the most promising next-generation batteries.

[0003] However, the solid sulfur cathode is reduced to soluble lithium polysulfide during discharge and then to solid lithium sulfide. The solid-liquid-solid transformation of the active material leads to a serious shuttle effect, which results in continuous consumption of the active material and rapid degradation of performance. In addition, the low utilization of active materials caused by the insulating property of sulfur is also an urgent problem to be solved. Various attempts such as constructing a porous conductive network, providing polar adsorption sites, and introducing catalytic sites have improved the utilization of active materials and suppressed the shuttle effect to a certain extent, but these problems cannot be fundamentally eliminated. Solid-solid conversion cathode materials represented by sulfurized polyacrylonitrile (SPAN) can fundamentally eliminate the shuttle effect and have received extensive research attention.

[0004] In view of this, this invention is proposed. Summary of the invention

[0005] The purpose of the present invention is to provide a new method for preparing a polyacrylonitrile positive electrode based on the existing polyacrylonitrile sulfide material, so as to reduce the content of long-chain sulfur in the polyacrylonitrile sulfide, improve the utilization rate of active substances in the polyacrylonitrile sulfide, and make the prepared polyacrylonitrile sulfide positive electrode have higher discharge specific capacity and cycle stability.

[0006] In order to achieve the above object, the present invention provides a method for preparing a sulfurized polyacrylonitrile positive electrode, which is carried out according to the following steps:

[0007] (1) dissolving polyacrylonitrile in an organic solvent and stirring until the polyacrylonitrile is completely dissolved to obtain a polyacrylonitrile solution;

[0008] (2) mixing and stirring the sulfide polyacrylonitrile, acetylene black and the polyacrylonitrile solution obtained in step (1) to obtain a mixture of sulfide polyacrylonitrile / acetylene black / polyacrylonitrile;

[0009] (3) evenly coating the mixture obtained in step (2) on aluminum foil, drying and cutting into positive electrode sheets;

[0010] (4) placing the positive electrode sheet obtained in step (3) in a sealed glass tube, heating it in an air environment at 200-350° C. for reaction, and taking it out and letting it cool naturally after the reaction is completed.

[0011] Preferably or optionally, the organic solvent used in step (1) is N-methylpyrrolidone.

[0012] Preferably or optionally, the concentration of polyacrylonitrile in the polyacrylonitrile solution prepared in step (1) is 20-40 g / L, preferably 20 g / L.

[0013] Preferably or optionally, the molecular weight of the polyacrylonitrile added in step (1) is 20,000-150,000.

[0014] Preferably or optionally, the mass ratio of sulfide polyacrylonitrile to acetylene black added in step (2) is 2-3.5:1, preferably 2:1.

[0015] Preferably or optionally, the mass ratio of the sulphurized polyacrylonitrile to the polyacrylonitrile solution added in step (2) is 3:20-30, preferably 3:25.

[0016] Preferably or optionally, the coating thickness in step (3) is 150-250 μm.

[0017] Preferably or optionally, the heating reaction time in step (4) is 3-6 h.

[0018] On the other hand, the present invention provides a sulfurized polyacrylonitrile positive electrode prepared by the above-mentioned preparation method.

[0019] In a third aspect, the present invention also provides the use of the above-mentioned sulfurized polyacrylonitrile positive electrode in a secondary battery.

[0020] Beneficial Effects

[0021] The invention adopts a liquid solution method to mix raw materials, uses polyacrylonitrile as a binder to achieve uniform mixing of the reaction raw materials in a liquid environment, and the sulfurized polyacrylonitrile is more evenly distributed in the polyacrylonitrile.

[0022] At the same time, the present invention also processes the sulfurized polyacrylonitrile positive electrode through a secondary sintering process, so that the long-chain sulfur in the sulfurized polyacrylonitrile is broken to form more short-chain sulfur, thereby improving the utilization rate of active substances in the sulfurized polyacrylonitrile.

[0023] Therefore, the sulfurized polyacrylonitrile positive electrode provided by the present invention achieves higher discharge specific capacity and cycle stability under the condition of unchanged sulfur content, and is very suitable for use as a positive electrode material for lithium batteries.

[0024] The preparation method of the sulfided polyacrylonitrile positive electrode provided by the present invention is simple, the raw material resources are abundant, and the structural components are controllable, and can be adjusted according to actual needs. The preparation process is simple to operate, the raw materials are easily available, and large-scale industrial production is easy, the cost is low, and there is no pollution to the environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a performance comparison diagram at different secondary sintering temperatures of the present invention.

[0026] Figure 2 This is a diagram showing the long cycle performance test results of Example 3 of the present invention. DETAILED DESCRIPTION

[0027] In order to facilitate the understanding of the present invention, the present invention will be described in more comprehensive and detailed manner below in conjunction with the accompanying drawings and preferred experimental examples, but the protection scope of the present invention is not limited to the following specific embodiments.

[0028] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0029] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0030] Example 1

[0031] The embodiment of the present invention provides a sulfurized polyacrylonitrile positive electrode.

[0032] 0.1 g of polyacrylonitrile powder with a molecular weight of 150,000 was weighed and added to 4.9 mL of N-methylpyrrolidone. The mixture was stirred magnetically for 60 min to prepare a polyacrylonitrile solution with a concentration of 20 g / L.

[0033] Weigh 0.6g of sulfide polyacrylonitrile and 0.3g of acetylene black powder and add them to the previously prepared polyacrylonitrile solution, and continue stirring for 5h. After stirring, use a coater to coat the mixture of sulfide polyacrylonitrile / acetylene black / polyacrylonitrile on an aluminum foil of size 5×10cm, with a coating thickness of 250μm. After coating, dry naturally and place in a vacuum oven at 60℃ for another 6h. After drying, use a cutting machine to cut the aluminum foil into pieces with a diameter of Ф=

[0034] 12mm positive electrode sheet.

[0035] The positive electrode sheet obtained by cutting is placed in a sealed glass tube and transferred to a muffle furnace, heated to 200°C in air for 6 hours. After the reaction is completed, it is taken out and cooled naturally to obtain a sulfide polyacrylonitrile positive electrode product.

[0036] Example 2

[0037] The embodiment of the present invention provides a sulfurized polyacrylonitrile positive electrode.

[0038] 0.1 g of polyacrylonitrile powder with a molecular weight of 150,000 was weighed and added to 4.9 mL of N-methylpyrrolidone. The mixture was stirred magnetically for 60 min to prepare a polyacrylonitrile solution with a concentration of 20 g / L.

[0039] Weigh 0.6g of sulfide polyacrylonitrile and 0.3g of acetylene black powder and add them to the previously prepared polyacrylonitrile solution, and continue stirring for 5h. After stirring, use a coater to coat the mixture of sulfide polyacrylonitrile / acetylene black / polyacrylonitrile on an aluminum foil of size 5×10cm, with a coating thickness of 250μm. After coating, dry naturally and place in a vacuum oven at 60℃ for another 6h. After drying, use a cutting machine to cut the aluminum foil into pieces with a diameter of Ф=

[0040] 12mm positive electrode sheet.

[0041] The positive electrode sheet obtained by cutting is placed in a sealed glass tube and transferred to a muffle furnace, heated to 250°C in air for 6 hours. After the reaction is completed, it is taken out and cooled naturally to obtain a sulfide polyacrylonitrile positive electrode product.

[0042] Example 3

[0043] The embodiment of the present invention provides a sulfurized polyacrylonitrile positive electrode.

[0044] 0.1 g of polyacrylonitrile powder with a molecular weight of 150,000 was weighed and added to 4.9 mL of N-methylpyrrolidone. The mixture was stirred magnetically for 60 min to prepare a polyacrylonitrile solution with a concentration of 20 g / L.

[0045] Weigh 0.6g of sulfide polyacrylonitrile and 0.3g of acetylene black powder and add them to the previously prepared polyacrylonitrile solution, and continue stirring for 5h. After stirring, use a coater to coat the mixture of sulfide polyacrylonitrile / acetylene black / polyacrylonitrile on an aluminum foil of size 5×10cm, with a coating thickness of 250μm. After coating, dry naturally and place in a vacuum oven at 60℃ for another 6h. After drying, use a cutting machine to cut the aluminum foil into pieces with a diameter of Ф=

[0046] 12mm positive electrode sheet.

[0047] The positive electrode sheet obtained by cutting is placed in a sealed glass tube and transferred to a muffle furnace, heated to 300°C in air for 6 hours. After the reaction is completed, it is taken out and cooled naturally to obtain a sulfide polyacrylonitrile positive electrode product.

[0048] Example 4

[0049] The embodiment of the present invention provides a sulfurized polyacrylonitrile positive electrode.

[0050] 0.1 g of polyacrylonitrile powder with a molecular weight of 150,000 was weighed and added to 4.9 mL of N-methylpyrrolidone. The mixture was stirred magnetically for 60 min to prepare a polyacrylonitrile solution with a concentration of 20 g / L.

[0051] Weigh 0.6g of sulfide polyacrylonitrile and 0.3g of acetylene black powder and add them to the previously prepared polyacrylonitrile solution, and continue stirring for 5h. After stirring, use a coater to coat the mixture of sulfide polyacrylonitrile / acetylene black / polyacrylonitrile on an aluminum foil of size 5×10cm, with a coating thickness of 250μm. After coating, dry naturally and place in a vacuum oven at 60℃ for another 6h. After drying, use a cutting machine to cut the aluminum foil into pieces with a diameter of Ф=

[0052] 12mm positive electrode sheet.

[0053] The positive electrode sheet obtained by cutting is placed in a sealed glass tube and transferred to a muffle furnace, heated to 350°C in air for 6 hours. After the reaction is completed, it is taken out and cooled naturally to obtain a sulfide polyacrylonitrile positive electrode product.

[0054] Comparative Example 1

[0055] This comparative example provides a sulfurized polyacrylonitrile positive electrode.

[0056] 0.1 g of polyacrylonitrile powder with a molecular weight of 150,000 was weighed and added to 4.9 mL of N-methylpyrrolidone. The mixture was stirred magnetically for 60 min to prepare a polyacrylonitrile solution with a concentration of 20 g / L.

[0057] Weigh 0.6g of sulfide polyacrylonitrile and 0.3g of acetylene black powder and add them to the previously prepared polyacrylonitrile solution, and continue stirring for 5h. After stirring, use a coater to coat the mixture of sulfide polyacrylonitrile / acetylene black / polyacrylonitrile on an aluminum foil of size 5×10cm, with a coating thickness of 250μm. After coating, dry naturally and place in a vacuum oven at 60℃ for another 6h. After drying, use a cutting machine to cut the aluminum foil into pieces with a diameter of Ф=

[0058] 12mm positive electrode sheet.

[0059] Effect Example 1

[0060] The sulfurized polyacrylonitrile positive electrodes prepared in Examples 1-4 and Comparative Example 1 were respectively used to assemble lithium-sulfur batteries.

[0061] The assembly process was carried out in an oxygen-free and water-free glove box. The shell was a CR2025 button battery shell. The positive electrode was the sulfide polyacrylonitrile positive electrode prepared in Example 1 and Comparative Example 1, respectively. The negative electrode was metallic lithium with a diameter of Ф=16 mm and a thickness of 2 mm. The diaphragm was a commercially available ordinary commercial diaphragm Celgard 2325 (diameter Ф=19 mm). 60 μL of electrolyte was added, and the composition of the electrolyte was EC / DEC=1:1 (volume ratio) + 1M LiPF6 + 5% FEC. After the assembly was completed, each battery was left to stand for 10 hours before performing relevant performance tests.

[0062] The cycle performance of each assembled battery was tested on the charge and discharge equipment. The specific test conditions were: the charge and discharge test was carried out at a current density of 0.2C. The test results are as follows: Figure 1 shown.

[0063] Depend on Figure 1 It can be seen that the discharge capacities of Examples 1-4 are much higher than those of Comparative Example 1, and the polyacrylonitrile sulfide positive electrodes that have undergone secondary sintering treatment all exhibit higher specific discharge capacities.

[0064] From the data of Example 1-4, it can be seen that with the increase of the secondary sintering temperature, the performance of the polyacrylonitrile sulfurized positive electrode is improved. When the temperature is greater than 300 degrees, the performance does not change much, indicating that the reaction is more complete at this time, and more long-chain sulfur in the polyacrylonitrile sulfurized is broken to form more short-chain sulfur.

[0065] Effect Example 2

[0066] The sulfurized polyacrylonitrile positive electrodes prepared in Example 3 and Comparative Example 1 were respectively used to assemble lithium-sulfur batteries.

[0067] The assembly process was carried out in an oxygen-free and water-free glove box. The shell was a CR2025 button battery shell. The positive electrode was the sulfide polyacrylonitrile positive electrode prepared in Example 1 and Comparative Example 1, respectively. The negative electrode was metallic lithium with a diameter of Ф=16 mm and a thickness of 2 mm. The diaphragm was a commercially available ordinary commercial diaphragm Celgard 2325 (diameter Ф=19 mm). 60 μL of electrolyte was added, and the composition of the electrolyte was EC / DEC=1:1 (volume ratio) + 1M LiPF6 + 5% FEC. After the assembly was completed, each battery was left to stand for 10 hours before performing relevant performance tests.

[0068] The long cycle performance of each assembled battery was tested on the charge and discharge equipment. The specific test conditions were: the charge and discharge test was carried out at a current density of 0.2C. The test results are as follows: Figure 2 shown.

[0069] Depend on Figure 2 It can be seen that although the coulombic efficiencies of Example 3 and Comparative Example 1 are similar, the coulombic efficiency of Comparative Example 1 becomes unstable as the number of charge and discharge cycles increases.

[0070] As for the specific capacity, although the specific capacity of Example 3 and Comparative Example 1 both decreases gradually with the increase of the number of charge and discharge cycles, the downward trend of Example 3 is better than that of Comparative Example 1, and the specific capacity performance of Example 3 in the entire test range is much higher than that of Comparative Example 1.

[0071] It can be seen from the above test results that the preparation method of the polyacrylonitrile sulfide positive electrode provided by the present invention, by adding a secondary sintering process to treat the polyacrylonitrile sulfide positive electrode, breaks the long-chain sulfur in the polyacrylonitrile sulfide to form more short-chain sulfur, thereby improving the utilization rate of the active substances in the polyacrylonitrile sulfide. Specifically, it achieves a higher discharge specific capacity and cycle stability under the condition of unchanged sulfur content, and has good application prospects.

[0072] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a sulfurized polyacrylonitrile positive electrode, characterized in that: Follow these steps: (1) dissolving polyacrylonitrile in an organic solvent and stirring until the polyacrylonitrile is completely dissolved to obtain a polyacrylonitrile solution; the concentration of the polyacrylonitrile in the polyacrylonitrile solution is 20 g / L; and the molecular weight of the polyacrylonitrile is 150,000; (2) mixing and stirring the sulfided polyacrylonitrile, acetylene black and the polyacrylonitrile solution obtained in step (1) to obtain a mixture of sulfided polyacrylonitrile / acetylene black / polyacrylonitrile; the mass ratio of sulfided polyacrylonitrile to acetylene black is 2:1; the mass ratio of sulfided polyacrylonitrile to the polyacrylonitrile solution is 3:25; (3) The mixture obtained in step (2) is evenly coated on aluminum foil, dried naturally and placed in a vacuum oven at 60° C. for further vacuum drying for 6 h, and then cut into positive electrode sheets after completion; (4) The positive electrode obtained in step (3) is placed in a sealed glass tube, heated at 300° C. in an air environment for reaction for 6 h. After the reaction is completed, the positive electrode is taken out and cooled naturally.

2. The method for preparing a sulfurized polyacrylonitrile positive electrode according to claim 1, characterized in that: The organic solvent used in step (1) is N-methylpyrrolidone or N,N-dimethylformamide.

3. The method for preparing a sulfurized polyacrylonitrile positive electrode according to claim 1, characterized in that: The coating thickness in step (3) is 150-250 μm.

4. A sulfurized polyacrylonitrile positive electrode, characterized in that: The invention is prepared by the preparation method described in any one of claims 1 to 3.

5. Use of the sulfurized polyacrylonitrile positive electrode described in claim 4 in a secondary battery.

Citation Information

Patent Citations

  • Method for improving performance of lithium sulfur battery by utilizing desolvation colloidal electrolyte

    CN103985902A

  • Positive electrode material for improving cycling stability of sulfurized polyacrylonitrile battery and preparation method of positive electrode material

    CN114702614A

  • Sulfur-containing positive electrode material slurry and preparation method thereof

    CN114824277A